Bidimensional Spectroelectrochemistry: application of a new device in the study of a o-vanillin-copper(II) complex - Izquierdo, D. (2017)
A new bidimensional spectroelectrochemistry setup for UV-Vis absorption measurements has been developed. The new device has been used to follow electrochemical reactions using two different arrangements: 1) a near-normal configuration that supplies information about the processes taking place both on the electrode surface and in the solution adjacent to it, and 2) a long-optical-pathway configuration based on a mobile slit that controls the position of a light beam passing parallel and adjacent to the electrode surface providing information only about the processes taking place in solution during the electrochemical reaction. The new setup has been validated using o-tolidine, a typical reference system for spectroelectrochemistry. The electrochemical mechanism of oxidation/reduction of Cu(o-Va)2(H2O)2 complex (o-Va = o-Vanillin = 2-hydroxy-3-methoxybenzaldehyde) has been studied using bidimensional UV-Vis absorption spectroelectrochemistry. This Cu(II) complex exhibits antimutagenic, anticarcinogenic and superoxide dismutase mimic properties.